2014
DOI: 10.1039/c4ib00239c
|View full text |Cite
|
Sign up to set email alerts
|

A biologically inspired lung-on-a-chip device for the study of protein-induced lung inflammation

Abstract: This study reports a biomimetic microsystem that reconstitutes the lung microenvironment for monitoring the role of eosinophil cationic protein (ECP) in lung inflammation. ECP induces the airway epithelial cell expression of CXCL-12, which in turn stimulates the migration of fibrocytes towards the epithelium. This two-layered microfluidic system provides a feasible platform for perfusion culture, and was used in this study to reveal that the CXCL12-CXCR4 axis mediates ECP induced fibrocyte extravasation in lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Developing in vitro models that accurately simulate the alveolar-capillary barrier of the lung is fundamental to achieve a better understanding of the mechanisms involved in pathophysiological conditions such as VILI. Previous reports have demonstrated the applicability of these types of biomimetic microsystems to conduct lung-nanotoxicology studies, their potential application for drug screening, and modeling of a wide range of lung inflammatory disorders 25 27 . However, these “lung-on-a-chip” (LOC) systems do not account for the complex nature of the lung ECM that consists of a compliant fibrous matrix and/or model the changes in the matrix that can occur during several lung disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Developing in vitro models that accurately simulate the alveolar-capillary barrier of the lung is fundamental to achieve a better understanding of the mechanisms involved in pathophysiological conditions such as VILI. Previous reports have demonstrated the applicability of these types of biomimetic microsystems to conduct lung-nanotoxicology studies, their potential application for drug screening, and modeling of a wide range of lung inflammatory disorders 25 27 . However, these “lung-on-a-chip” (LOC) systems do not account for the complex nature of the lung ECM that consists of a compliant fibrous matrix and/or model the changes in the matrix that can occur during several lung disorders.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the propagation and rupture of liquid plugs, which simulated the reopening of closed airways in the absence of pulmonary surfactant, cause mechanical stress on harmful fluids, resulting in serious damage to small airway epithelial cells; in addition, explosive pressure waves generated by plug rupture were shown to facilitate detection of mechanical cell damage using a stiff sound. In addition, Punde et al [57] proposed a biomimetic microsystem that reconstructs the lung microenvironment to monitor the role of eosinophil cationic protein (ECP) in lung inflammation. ECP induces airway epithelial cells to express CXCL12 and stimulates the migration of fibroblasts toward the epithelium.…”
Section: Microfluidic Chip-based Air-liquid Interface Respiratory Modelmentioning
confidence: 99%
“…As far as the onset of lung diseases is concerned, researchers are focused in producing biomimetic microsystems so that the molecular processes underlying pathologies such as malignant transformation of bronchial epithelial cells due to tobacco [ 84 ], protein-induced lung inflammation [ 80 ], chronic obstructive pulmonary disease [ 81 ] and idiopathic pulmonary fibrosis [ 85 ] can be highlighted.…”
Section: Convergence Between Microfluidics and Tissue Engineering:mentioning
confidence: 99%